Effect of Normobaric Oxygen Inhalation Intervention on Microcirculatory Blood Flow and Fatigue Elimination of College Students After Exercise - Peng, Yong; Meng, Liang; Zhu, Huan; Wan, Li; Chen, Fen (Frontiers in Genetics, 2022)
To explore the effect of normobaric oxygen inhalation intervention on microcirculatory blood flow of college students after exercise and the impact of the elimination of exercise-induced fatigue,to provide a theoretical and methodological reference for the rapid elimination of fatigue of college students after endurance exercise. Methods: Forty-eight male non-sports majors of Hubei University for nationalities were randomly divided into the control group (n = 24) and intervention group (n = 24). The subjects in both groups completed the same exercise program twice (running 3000 meters on the treadmill at maximum speed). After running, the issues in the intervention group inhaled portable oxygen for 30 minutes, and the control group recovered naturally. Microcirculatory blood flow (MBP), blood flow velocity (AVBC), blood flow concentration (CMBC), muscle oxygen saturation (SmO2), heart rate (HR), blood lactic acid (BLA), blood urea (BU), and creatine kinase (CK) were measured before exercise, immediately after exercise and 30 minutes after exercise.